Development of Saintific-based Students’ Worksheet (LKS) by Utilizing the Ferns Taxonomy Garden as a Supplementary of Plantae Teaching Material (Journal of Innovative Science Education, 2019)
MA Al Asror Semarang has a fern taxonomy garden that can be used for observing Plantae material, especially Pteridophyta, but doesn’t yet have a student’s worksheets that can direct the activity process. This study aims to develop student’s worksheets (LKS) based on a scientific approach and testing the validity, practicality and effectiveness. This study uses the Research and Development (R&D) approach with the ADDIE model. Validity of student’s worksheets is obtained from media experts, practicality is measured by teacher and student responses and effectiveness is measured by student learning outcomes. The results show that the students’ worksheets was declared 'very valid' with an average score of 94.10%, 'very practical' by teachers and students responses with an average score of 82,66% and effective as a supplement for teaching materials because it can improve cognitive learning outcomes of students with N-gain of 0.58 (criteria 'medium') and optimize psychomotor learning outcomes of students with an average score of 86.34% (criteria 'very good' ). Based on the results of the study, scientific-based student’s worksheets by utilizing a fern taxonomy garden stated as worthy to be used as a supplement of teaching material for Plantae at the MA Al Asror Semarang.